1998
DOI: 10.1097/00004714-199802000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Venlafaxine in the Treatment of Major Depression and Major Depression Associated With Anxiety

Abstract: This 12-week, double-blind, placebo-controlled study evaluated the efficacy and safety of venlafaxine as first-line therapy for the treatment of major depression and major depression associated with anxiety in 384 adult outpatients. Fixed total daily dosages of 75, 150, and 200 mg of venlafaxine were administered in a twice-a-day regimen. Primary efficacy parameters were the Hamilton Rating Scale for Depression (HAM-D) total score, the HAM-D Depressed Mood Item, the Montgomery-Asberg Depression Rating Scale to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 8 publications
3
40
0
1
Order By: Relevance
“…The results of this study reflect findings of formal studies of treatment-resistant depression (Nierenberg et al, 1994;Poirier et al, 1999), where higher doses of venlafaxine were found to be effective. The mechanism of venlafaxine's apparent efficacy in treating resistant…”
Section: Commentssupporting
confidence: 78%
See 2 more Smart Citations
“…The results of this study reflect findings of formal studies of treatment-resistant depression (Nierenberg et al, 1994;Poirier et al, 1999), where higher doses of venlafaxine were found to be effective. The mechanism of venlafaxine's apparent efficacy in treating resistant…”
Section: Commentssupporting
confidence: 78%
“…Venlafaxine is an effective antidepressant (Khan et al, 1998;Schweizer et al, 1991) that may have some advantages over other antidepressants. Comparative studies against amitriptyline (Gentil et al, 2000) report no difference in efficacy in treating depressive symptoms, whereas comparisons with imipramine (Shrivastava et al, 1994) and fluoxetine (Clerc et al, 1994) have suggested venlafaxine to be significantly superior in certain populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A fixed dose-response study with sertraline failed to find a dose-response relationship with doses from 50 mg/day to 200 mg/day [Sheikh et al, 2000], whereas a fixeddose study with paroxetine reported significant separation from placebo at 40 mg/day but not at 20 mg/day [Ballenger et al, 1998b]. Venlafaxine has demonstrated a positive dose-response relationship for the treatment of major depression [Kelsey, 1996;Khan et al, 1998;Rudolph et al, 1998], and it is possible that such a response would also be observed among patients with panic and comorbid major depression treated with venlafaxine ER. However, this issue cannot be addressed in this study, which excluded patients with significant depression.…”
Section: Discussionmentioning
confidence: 99%
“…Starting therapy at lower dosages and gradually titrating upward can minimize nausea, the most common side effect; nausea also diminishes with time after the maintenance dosage has been reached. 16,23,24 Studies have shown that a response to venlafaxine can occur as early as week 1. 23 As the result of a positive doseresponse curve, increasing the dosage has been shown to increase rates of response and remission.…”
Section: Pharmacologic Therapymentioning
confidence: 99%